The Forecasting of the Development of Suffosion Processes in Urban on the Basis of the Geoelectric Modeling by the Data of the Phasometric System of the Geodynamic Control - V. Dorofeev, Nikolay; R. Kuzichkin, Oleg; V. Grecheneva, Anastasia; D. Bakni, Maxim (International Journal of Engineering and Technology, 2018)
In this article, techniques and algorithms of the control and forecasting of the karst risk of the territory are considered. The formation of forecast assessments of the development of suffosion processes is carried out on the basis of the computer modeling with the correction of model data on the flexible schedule by results of the monitoring. To reduce the costs of the monitoring work, the resistive control method is proposed to use. This method is based on the phasometric principle of the control of the development of suffosion processes. In the article causes and stages of the development of suffosion processes are gives, features of the development and the control of suffusion processes are described for urban territories. The modeling of suffosion processes is carried out on the basis of the geoelectrical model of the spherical cavity of the covered thickness of soil sediments. The description of the experimental setup is given for the modeling of the suffosion processes and for the control of their formation by the phase control method. The estimation of the adequacy of results is obtained.The approbation of the proposed algorithm was carried out at the site of the alleged development of man-made suffusion processes. The identification and localization of the suffosion processes took place on the basis of the risk map and the phaseometric control method. The correction of the model was carried out by the data of the georadar survey of the investigated area. The proposed algorithm allows minimizing the costs of monitoring activities and increases the accuracy of forecast estimates during the modeling the geological environment on simple models.Â Â